Roles of transcriptional factor PsrA in the regulation of quorum sensing in Pseudomonas aeruginosa PAO1 - Kok, Li-Ching; Tsai, Chia-Chun; Liao, Yu-Hsuan; Lo, Yi-Ling; Cheng, Nai-Wei; Lin, Ching-Ting; Chang, Hwan-You (Frontiers in Microbiology, 2024)
The transcription factor PsrA regulates fatty acid metabolism, the type III secretion system, and quinolone signaling quorum sensing system in Pseudomonas aeruginosa. To explore additional roles of PsrA in P. aeruginosa, this study engineered a P. aeruginosa PAO1 strain to carry a recombinant plasmid with the psrA gene (pMMBpsrA) and examined the impact of elevated psrA expression to the bacterium. Transcriptomic analysis revealed that PsrA significantly downregulated genes encoding the master quorum-sensing regulators, RhlR and LasR, and influenced many quorum-sensing-associated genes. The role of PsrA in quorum sensing was further corroborated by testing autoinducer synthesis in PAO1 [pMMBpsrA] using two reporter bacteria strains Chromobacterium violaceum CV026 and Escherichia coli [pSB1075], which respond to short-and long-chain acyl homoserine lactones, respectively. Phenotypic comparisons of isogenic ∆psrA, ∆lasR, and ∆psrA∆lasR mutants revealed that the reduced elastase, caseinase, and swarming activity in PAO1 [pMMBpsrA] were likely mediated through LasR. Additionally, electrophoretic mobility shift assays demonstrated that recombinant PsrA could bind to the lasR promoter at a 5'-AAACGTTTGCTT-3' sequence, which displays moderate similarity to the previously reported consensus PsrA binding motif. Furthermore, the PsrA effector molecule oleic acid inhibited PsrA binding to the lasR promoter and restored several quorum sensingrelated phenotypes to wild-type levels. These findings suggest that PsrA regulates certain quorum-sensing phenotypes by negatively regulating lasR expression, with oleic acid acting as a crucial signaling molecule.